Marble Dust Exposure Relationship to Workers‘ Lung Conditions in Marble Industries - Ummul Khoiroh (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: Marbel mining in Tulungagung caused air quality pollution of dust. The level of air pollution in the marble industrial mining area in Besole village, Tulungagung, was a high category. Air pollutions from dust cause fibrosis in the lungs if continuously inhaled. This marble dust belongs to the group of differentiative dust”pulmonary disorders due to dust in the form of restriction, obstruction, or mixture of the two. The study aims to analyze the internal factors related to lung conditions in one of the Besole Village industries, Tulungagung. Method: research that has been done using cross-sectional design through a quantitative approach. Determination of the sample size by simple random sampling. Twenty-four workers consisting of 12 exposed and 12 were not exposed to dust. Result and Discussion: The results of measurements of marble dust levels in the study area were 20,000 mg/m3, which exceeds the specified threshold value. Meanwhile, the statistical test value p= 0.000 means a relationship between dust levels and the condition of workers' lungs in the exposed area. Most workers' lung conditions in one of the Besole village industries are quite good. Conclusion: The condition of the lungs is closely related to dust levels that exceed the threshold value. The lungs' condition is also influenced by work time and poor behavior, namely the habit of not wearing PPE and smoking habits, causing decreased lung function.